2019
DOI: 10.3390/ijms20071534
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of Gut Hormones, Ghrelin and Obestatin in Oral Mucositis

Abstract: Chemotherapy and/or head and neck radiotherapy are frequently associated with oral mucositis. Oral pain, odynophagia and dysphagia, opioid use, weight loss, dehydration, systemic infection, hospitalization and introduction of a feeding tube should be mentioned as the main determinated effect of oral mucositis. Oral mucositis leads to a decreased quality of life and an increase in treatment costs. Moreover, oral mucositis is a life-threatening disease. In addition to its own direct life-threatening consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 283 publications
(385 reference statements)
0
14
0
Order By: Relevance
“…The dentist who attends cancer patients should examine pre-existing oral conditions and treat them before chemotherapy, as well as remove foci of infection, instructing and motivating the correct oral hygiene. When OM is installed, several therapeutic options are available, including low-level laser, cryotherapy, antioxidant drugs, growth factors, and PTA (polymyxin, tobramycin and amphotericin B) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The dentist who attends cancer patients should examine pre-existing oral conditions and treat them before chemotherapy, as well as remove foci of infection, instructing and motivating the correct oral hygiene. When OM is installed, several therapeutic options are available, including low-level laser, cryotherapy, antioxidant drugs, growth factors, and PTA (polymyxin, tobramycin and amphotericin B) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential protective and therapeutic effects of ghrelin on oral mucositis were reported. The concentrations of ghrelin in saliva are similar or higher than plasma, a decreased saliva secretion in patients under chemotherapy or radiology makes them prone to develop oral mucositis [50]. Furthermore, experimental studies performed on rats have shown that intraperitoneal administration of ghrelin accelerated the healing of oral ulcers.…”
Section: Antioxidant and Protective Effect Related To The Gastrointestinal Tractmentioning
confidence: 99%
“…The plasma level of ghrelin is negatively correlated with BMI and food intake. For this reason, the plasma concentration of ghrelin is enhanced by anorexia nervosa, starvation, and cachexia, while obesity leads to the opposite effect [ 44 ]. Food intake decreases the plasma ghrelin levels, however the degree of this reduction depends on the type of nutrients present in the food.…”
Section: Physiological Action Of Ghrelinmentioning
confidence: 99%
“…The effect of ghrelin on pancreatic endocrine secretion was initially unclear. Early studies have shown that ghrelin increases insulin secretion by pancreatic β-cells [ 44 , 57 , 58 ], while next studies have reported that ghrelin inhibits insulin release in the islets of Langerhans [ 44 , 59 , 60 ]. Currently, it is commonly accepted that ghrelin inhibits glucose-dependent insulin secretion, acting directly on beta-cells in pancreatic islets [ 44 , 61 , 62 ].…”
Section: Physiological Action Of Ghrelinmentioning
confidence: 99%